Computer Programming and Basic Education (Alternate Horizons, 2021)
In our world today, many basic skills are taught to the youth-skills such as mathematics, physical sciences and language, just to name a few. In this paper, I will explore a few reasons why computer programming should be added to this list.
Keywords: computer programming; basic education